Virulence of selected indigenous Metarhizium pingshaense (Ascomycota: Hypocreales) isolates against the rice leaffolder, Cnaphalocrocis medinalis (Guenèe) (Lepidoptera: Pyralidae). (January 2018) - Kirubakaran, Suyambulingam Arunachalam; Abdel-Megeed, Ahmed; Senthil-Nathan, Sengottayan
Abstract: The aim of this study was to screen and select Metarhizium spp. for the effective management of rice pest Cnaphalocrocis medinalis Guenèe. The virulent screening assay with nine Metarhizium soil isolates at the concentration of 1 × 10 8 conidia/ml on third-instar larvae of C. medinalis have shown that isolates RMT4 and RMT10 caused significant mortality (above 90%) with shorter lethal time than other isolates tested. Molecular sequencing of the EFα-1 region of high virulent Metarhizium isolates RMT4 and RMT10 have confirmed that these isolates belong to the species M. pingshaense . The effect of the two virulent M. pingshaense (RMT4 and RMT10) isolates on larvae development, food consumption of C. medinalis was studied. Larvae were susceptible to both fungal isolates, causing the same level of mortality. In larvae the first instars were the most sensitive with shorter lethal times, while the longest lethal time occurred in fourth instars. Estimation of the LC50 on third instars, showed a lower LC50 for RMT10 treatment than RMT4. Both isolates (RMT4 and RMT10) caused reduced growth and food consumption on third instars. Nutritional indices were declined significantly, but the approximate digestibility (AD) of treated larvae was significantly higher with increase concentration of the fungal conidia (1 × 10 4, 1 × 10 5 and 1 × 10 6 ). The M. pingshaense isolates are known to cause lethal effects on the pupae of C. medinalis . The RMT10 showed lower LC50 value of 7.94 × 10 5 conidia/ml on pupae than RMT4, which is 2.75 × 10 6 conidia/ml. The M. pingshaense RMT10 exhibited greater potential as a treatment against C. medinalis, rice leaf folder (RLF). Graphical abstract: Highlights: High virulent isolates (RMT4 and RMT10) were identified as M. pingshaense through comparative gene sequencing, (EFα-1, elongation factor 1-alpha). Treated larvae and pupae were susceptible to the M. pingshaense in dose-dependent manner. M. pingshaense affected food consumption of third-instars of C. medinalis . M. pinghanese (RMT10) was the more effective isolate against C. medinalis .